Remodelação de biomarcadores imunológicos em pacientes com hepatite C crônica tratados com agentes antivirais de ação direta - Isabela Gomes Ribeiro (2020)
Remodeling of immunological biomarkers in patients with chronic hepatitis C treated with direct acting antiviral therapy Background &Aims: The HCV treatment with direct-acting antiviral agents (DAAs) has offered a unique opportunity to analyze the changes in the immune system caused by the rapid inhibition of viral replication. We sought to analyze the kinetics profiles of serum biomarkers in patients with chronic hepatitis C upon DAAs treatment. Methods: Fifty HCV patients were enrolled in a longitudinal investigation carried out before (baseline), during (W2-4 and W8-12 weeks) and post-treatment (W12-24 weeks) with sofosbuvir plus daclatasvir ± ribavirin (n=36) or simeprevir (n=14). Distribution of HCV genotypes 1a/b, 2 and 3 was 80%, 6% and 14%, respectively. All patients had SVR. Fifteen uninfected blood donors formed the control group (NI). Serum biomarkers CXCL8, CCL11, CCL3, CCL4, CCL2, CCL5, CXCL10, IL-1β, IL-6, TNF-α, IL-12, IFN-γ, IL-15, IL-17, IL1Ra, IL-4, IL-5, IL-9, IL-10, IL-13, FGF-basic, PDGF, VEGF, G-CSF, GM-CSF, IL-7 e IL-2 were quantified by Luminex Bio-Plex Pro™ platform. Mann-Whitney (HCV and NI), Kruskal Wallis (multiple), and Dunn (sequential in pairs) tests were used for comparisons between groups. The significance considered was p≤0.05. The Prism Graph Pad 8.0 software was used for statistical analysis and graphic arts. The study was approved by the institutional and ethical boards of UFMG and FIOCRUZ/Minas. All participants signed the consent form. Results: The results demonstrated a clear biomarker remodeling in HCV patients at baseline as compared to NI, characterized by high levels of chemokines, pro-inflammatory cytokines, and growth factors, with minor increase of regulatory cytokines. The kinetics timeline of baseline fold changes upon DAAs treatment revealed an early decline of CXCL8, CCL4, IL6, IL-15, IL-17, IL-9, GM-CSF and IL-7 at W8-12 and a late remodeling of CCL3, CCL2, CCL5, IL1β, TNF-α, IL-12, IFN- γ, IL1-Ra, IL-4, IL-10, IL-13, PDGF, VEGF, G-CSF at W1224. ALT ≥69U/L, platelet ≤150,000/mm3 and liver cirrhosis at baseline were factors related to delayed immune response remodeling. Conclusions: The HCV eradication with DAAs results in a profound readjustment of the microenvironment of serum biomarkers of the immune response, which is notable in patients with chronic hepatitis C, and may be slower in those with compensated cirrhosis and high ALT levels. These results add evidence to the knowledge of the process of immune remodeling associated with the rapid viral eradication of HCV with the current potent antiviral drugs.